STRATEGI PERUSAHAAN DALAM PENANGANAN BERKURANGNYA FOKUS PEGAWAI DI KECAMATAN GUNUNGPATI - Minarsih, Maria Magdalena (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2019)
Human resources is one of the determinants of the success of the company because the role of human resources as a valuable asset is to plan, implement and control various operational activities of the company. The problem that arises when one manages human resources is one that can cause a decrease in focus which results in a decrease in employee performance, therefore the company needs to have several strategies to solve the problem. This study aims to find out strategies that can be applied by SMEs in Gunungpati in the face of reduced employee focus. Strategies that can be applied include factors such as job satisfaction, work environment, work compensation and stres. The object of this research is UKM in Gunungpati. Data collection was conducted through questionnaires by SME employee respondents in the Gunungpati region. The analytical method used is multiple linear regression analysis. The results of this study indicate that (1) Job satisfaction, work environment, compensation, and work stres partially have a positive and significant effect on employee focus. (2) Job satisfaction, work environment, compensation, and work stres simultaneously have a positive and significant effect on employee focus.